Political Tolerance and Conflict Reconciliation Practices: Lesson Learnt from Mamasa, Eastern Indonesia - Mahyuddin, Mahyuddin; bin Mohd Nizah, Mohd Azmir; Mohad Ramli, Abd. Hakim Mohad Ramli (UIN Sunan Gunung Djati Bandung, 2025)
Political conflicts involving religious identities have remained a persistent challenge in Indonesia, where social diversity often intersected with political contestation. This study examined ethnoreligious reconciliation mechanisms and practices of political tolerance observed during regional head elections (Pilkada) and in everyday interfaith relations in Mamasa, West Sulawesi. Although Mamasa experienced electoral polarization and episodes of political tension in the post-reform era, local wisdom and customary law have played a central role in promoting more peaceful and inclusive democratic practices. This research employed a qualitative case study design, collecting data through in-depth interviews with 12 key informants—religious leaders, customary authorities, local government actors, and voters—supplemented by secondary sources. Data were analyzed using an inductive thematic approach that involved coding, categorization, and cross-case interpretation to understand how customary values shaped political behavior and conflict management. The findings have shown that Mamasa’s socio-cultural structure—rooted in inclusive dialogue, religious plurality, and customary mediation—has provided an effective informal mechanism for maintaining social harmony. Communities consistently elected interfaith candidates to regional leadership positions and created spaces for interreligious interaction that have supported processes of conflict reconciliation. These locally grounded practices reflected broader discourses on identity politics, peacebuilding, and democratic resilience. The practical significance of this study lies in demonstrating that culturally rooted reconciliation models can complement formal governance structures. Such approaches offer policymakers, local governments, and peacebuilding practitioners actionable insights for managing ethnoreligious tensions and strengthening democratic stability in pluralistic and post-conflict regions.